Innovative public-private partnership on climate information services reaches 500,000 fisherfolks and farmers in Senegal - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
CCAFS worked with national public (ANACIM) and private partners (Jokalante, Meteo-Mbay) in Senegal to design and disseminate tailored climate information services (CIS) through SMS and voice messages. These services help support farm management decision making by farmers and warn artisanal fisherfolk about extreme weather events at sea.